EVALUATION OF THE SPREAD OF RADICALISM, EXTREMISM, AND TERRORISM IN INDONESIA'S DEFENSE USING AGENT-BASED SIMULATIONS - Nurdiansyah, Hendra; Almubaroq, Hikmat Zakky; Risdhianto, Agung; Mualim, Much (Sanata Dharma University, 2023)
The issue of national disintegration is one of the most crucial in the defense of Indonesia. One of the causes of national disintegration is the existence of Radicalism, Extremism, and Terrorism (RET). Radical entities can change using extreme means including violence through acts of terror in achieving their goals. Efforts continue to be made by the Government in anticipating the spread of this RET. Using agent-based simulation modeling techniques, some characteristics in the RET such as numbers are affected, driving factors, the number of agents in a region, and effective strategies. Therefore, this study is aimed at evaluating the spread of RET in Indonesia using agent-based simulations. This research is qualitative descriptive by trying to collect qualitative data as an initial input for the creation of flowchart designs and agent-based simulation models that will eventually be verified and validated. The results of this study illustrate the agent-based simulation in the spread of RET using Netlogo software by paying attention to several parameters such as incubation period, possible exposure to radicalism, extremist severity, availability of rehabilitation centers, and the rate of terrorism infection. From the results of the simulation, it can be said that the parameter greatly affects the percentage of radical agents, agents who are extremists until they become terrorists. This factor can be evidence for policymakers to reduce the spread of RET effectively by increasing religious understanding, strengthening the sense of nationalism and defending the country, and implementing community empowerment strategies. The evaluation of the spread of this RET can eventually strengthen Indonesia's non-military defense. Thus, good defense will have implications for the continuous development and achievement of Indonesia's goals.